2015
DOI: 10.1136/bjophthalmol-2014-306485
|View full text |Cite
|
Sign up to set email alerts
|

Re-appraisal of topical 1% voriconazole and 5% natamycin in the treatment of fungal keratitis in a randomised trial

Abstract: Clinical Trial Registry India (2010/091/003041).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 18 publications
2
52
0
4
Order By: Relevance
“…Increasing the concentration of voriconazole eye drops may lead to increased efficacy and/or reduced dosing frequency; however, the benefit of using concentrations greater than 1% has not been evaluated in patients with fungal keratitis . In a comparative study conducted by mycotic ulcer treatment trial group natamycin treatment was associated with significantly better clinical and microbiological outcomes than voriconazole treatment for smear-positive filamentous fungal keratitis, with much of the difference attributable to improved results in Fusarium cases and similar results were also found in another randomized trial conducted by Sharma S et al 22,23 B.Intrastromal route After administration of peribulbar anesthesia, under full aseptic conditions, the preloaded drug should be Table 3. Method of dilution for intravitreal, intracameral and intrastromal preparations.…”
Section: A Topical Eye Dropsmentioning
confidence: 85%
“…Increasing the concentration of voriconazole eye drops may lead to increased efficacy and/or reduced dosing frequency; however, the benefit of using concentrations greater than 1% has not been evaluated in patients with fungal keratitis . In a comparative study conducted by mycotic ulcer treatment trial group natamycin treatment was associated with significantly better clinical and microbiological outcomes than voriconazole treatment for smear-positive filamentous fungal keratitis, with much of the difference attributable to improved results in Fusarium cases and similar results were also found in another randomized trial conducted by Sharma S et al 22,23 B.Intrastromal route After administration of peribulbar anesthesia, under full aseptic conditions, the preloaded drug should be Table 3. Method of dilution for intravitreal, intracameral and intrastromal preparations.…”
Section: A Topical Eye Dropsmentioning
confidence: 85%
“…In cases of fungal keratitis, voriconazole 100 lg/mL may be used to irrigate the flap interface, as well as topically [21]. Others have reported commercially available natamycin 5 % may work at least as well in topical administration as topical voriconazole in many cases of keratomycosis, although its specific use for post-refractive surgery organisms requires further study [38][39][40].…”
Section: Treatmentmentioning
confidence: 96%
“…Voriconazole is a good choice for the treatment of FK due to deep penetration in all tissues. Treatment with voriconazole in over 40 clinical cases with a broad range of fungal pathogens resistant to some antifungals like amphotericin B was reported (57). In studies comparing voriconazole and natamycin, no significant differences were found in scar size and perforations in patients treated with voriconazole and natamycin (58), but natamycin was found to be more effective in visual acuity and healing corneal ulcers (59).…”
Section: Treatmentmentioning
confidence: 99%
“…In the ophthalmic literature, the use of voriconazole and amphotericin B topical was reported for the treatment of filamentous FK (51,55). Voriconazole had more permeability than natamycin in penetration in intact epithelium (55,57). Natamycin suspension (5 mg/mL) and amphotericin B drop (1.5 mg/mL) have been used for the treatment of topical FK (60).…”
Section: Treatmentmentioning
confidence: 99%